First case of Strongyloides stercoralis infection in a dog in the Republic of Macedonia - Aleksandar Cvetkovikj; Ljubica Rashikj; Irena Celeska; Elena Atanaskova Petrov; Branko Angjelovski; Iskra Cvetkovikj; Maja Jurhar Pavlova; Jovana Stefanovska (Macedonian Veterinary Review, 2018)
A six-month-old Pomeranian male dog was referred due to a month long history of unformed, soft faeces and mild weight loss. Stool analyses by direct faecal smear, Zinc sulphate flotation and the Baermann concentration method revealed an infection with Strongyloides stercoralis. The dog was initially treated once with a combination drug of praziquantel, pyrantel and febantel (½ Drontal® Plus Tablets for puppies and small dogs; Bayer; i.e. 31.5 mg/kg bodyweight of febantel). The treatment was repeated after 12 days with the same dosage for 3 consecutive days. The stool analyses performed 14 days and 3 months after the second treatment were negative for S. stercoralis larvae. The results suggest that a repeated treatment with Drontal® Plus Tablets is effective against S. stercoralis in dogs and has no adverse effects.